Bax expression is a candidate prognostic and predictive marker of colorectal cancer - Katkoori, Venkat R; Suarez-Cuervo, Catalina; Shanmugam, Chandrakumar; Jhala, Nirag C; Callens, Tom; Messiaen, Ludwine; III, James Posey; Bumpers, Harvey L; Meleth, Sreelatha; Grizzle, William E; Manne, Upender (Journal of Gastrointestinal Oncology; Vol 1, No 2 (December 13, 2010): Journal of Gastrointestinal Oncology, 2010)
Objective: Since the anti-tumor activity of 5-fluorouracil (5-FU) is due to induction of apoptosis, we assessed the value of expression of key apoptotic molecules (Bax, Bcl-2 and p53) in predicting the efficacy of 5-FU therapy for colorectal adenocarcinomas (CRCs). Methods: Archival tissues of CRCs from 56 patients who received a complete regimen of 5-FU-based chemotherapy after surgery, and 56 patients matched for age, gender, ethnicity, tumor stage, tumor location, and tumor differentiation who had undergone only surgery (without any pre- or post-surgery therapy), were evaluated for immunophenotypic expression of Bax, Bcl-2, and p53. Also, these CRCs were evaluated for Bax mutations. The predictive capacity or prognostic value of these markers was assessed by estimating overall survival. Results: The majority of low Bax expressing CRCs have exhibited mutations at the G (8) tract. There was no significant difference in overall survival rates between the categories of surgery alone and 5-FU-treated patients. However, a better survival was observed for patients who received chemotherapy when their CRCs had low Bax/Bcl2 ratio (HR, 1.55; 95% CI: 1.46-31.00). Patients who received surgery alone and whose CRCs lacked Bax expression had 5.33 times higher mortality than those with high Bax expression (95% CI: 1.78-15.94), when controlled for tumor stage and other confounders. Bcl-2 and nuclear p53 accumulation had no predictive value in either patient group. Conclusion:These findings are the first to demonstrate that high Bax expression is a good prognosticator for patients who underwent surgery alone, and that patient with low Bax/Bcl-2 expression ratio benefit from 5-FU-based adjuvant therapies.